1980
DOI: 10.1007/bf02408524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of castration on the bone structure of male rats: A model of osteoporosis

Abstract: Forty young (23-day-old) and thirty old (1-year-old) male rats were castrated and sacrificed with controls at intervals up to 18 months of age. No differences were observed between femurs or mandibles of rats castrated at 23 days and those of controls. Year-old castrate rats developed femoral osteoporosis after 2 months, which became more pronounced 4 months after castration. This was characterized by reductions in femoral density, dry weight, dry weight per unit length, and ash weight, and by the appearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(72 citation statements)
references
References 19 publications
5
64
1
2
Order By: Relevance
“…As age-, gender-, and muscle-specific differences could be found in the response to PTH treatment, the effect of PTH on metabolic and structural properties of the two limb muscles gastrocnemius and soleus and the back muscle longissimus was analyzed. Rats display deleterious changes in bone 4 weeks after orchiectomy (Turner et al 1989) and represent a valuable experimental model for osteoporotic studies (Wink & Felts 1980). The clear decrease in serum testosterone verified the success of orchiectomy in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…As age-, gender-, and muscle-specific differences could be found in the response to PTH treatment, the effect of PTH on metabolic and structural properties of the two limb muscles gastrocnemius and soleus and the back muscle longissimus was analyzed. Rats display deleterious changes in bone 4 weeks after orchiectomy (Turner et al 1989) and represent a valuable experimental model for osteoporotic studies (Wink & Felts 1980). The clear decrease in serum testosterone verified the success of orchiectomy in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Much evidence has shown that BMD decreases with increasing age in men, and is accompanied by decreasing sex hormones, but more moderately than in post-menopausal women [5,10,17,18,23,24]. According to previous studies, the high BMD or calcium content of the first and fourth lumbar vertebrae, femur, and tibia coincided with a high testosterone level at the age of 12 months in male Wistar rats [11,14,17].…”
Section: Discussionmentioning
confidence: 98%
“…This method has already been used in rat (Wink & Felts 1980, Ortoft & Oxlund 1988 and fish (Casadevall et al 1990, for studying bone demineralization. In the Japanese eel, Yamada et al (2002) demonstrated by this method that the mineral content (phosphorus and calcium) in bone tissue decreased during experimental sexual maturation.…”
Section: Cortisol-induced Eel Vertebral Demineralizationmentioning
confidence: 99%